Clinical, laboratory and neurological assessment of lithium toxicity in patients with bipolar disorders - El-sayed Hamdey El-sayed Gawesh; Samir Atef Farid Elmetwally; Ahmed Ibrahim Elshoura; Mokhtar Ahmed Mokhtar Abo-Elfotoh; Medhat Mohamed Abdelsalam Darwish; Shaymaa Mohammed Arafa; Ismail Sadek; Doaa Ibrahim Hassan Ibrahim; Aisha Ghanem Abd El Lateef; Mona M. Amin; Maryam Mohammed Mohammed Hamouda; Hanan Ahmed Abd Almohymen ALfiky; et al. (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Lithium was once the drug of choice for treating bipolar disorder. It has a low therapeutic efficacy and frequently appears in hazardous concentrations in clinical practice. It has been found that long-term lithium intoxication, which is caused by lithium gradually building up, is more common. The overwhelming majority of the symptoms are neurological; commonly, the mental state is disturbed and could even become coma-like.Aim: To measure the clinical, laboratory, and neurological changes of lithium toxicity in patients with bipolar disorder in correlation with these effects with periodic lithium level monitoring.Methods: In order to pinpoint individuals with euthymic BD based on various serum concentrations (3 mmol/L), the cohort research was carried out in Al Azhar New Damietta Hospital from September 1, 2022 to the end of January 2023. Disease was confirmed using the Young Mania Rating Scaling (YMRS) and the structured diagnostic examination for DSM-V axis I disorders.Demographic, clinical, and laboratory data were obtained for analysis.Results: The distribution of severe/moderate/mild neurological symptoms for the >3 mmol/L, 1.2– 3 mmol/L and 3 mmol/L of lithium than those receiving 1.2–3 mmol/L and 3 mmol/L, p